(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
A new small biseriamminoid foraminifer, Globigaetania angulata gen. n. sp. n., is here described from the Wordian of a Permian–Triassic sedimentary succession of NW Iran (Zal and Poldasht stratigraphic sections). The new taxon, dedicated to Prof. Maurizio Gaetani, is characterised by peculiar morphology, coiling, and structures that are characteristic of the subfamily Globivalvulininae Reitlinger, 1950, family Globivalvulinidae Reitlinger, 1950, superfamily Biseriamminoidea Chernysheva, 1941. The introduction of the new taxon contributes to the knowledge of the systematics and evolution of the Palaeozoic biserial microgranular foraminifera.